Development of an Educational Video of Air Conditioning Workshop Practice using the YouTube Platform - Hamzah, Siti Nurulhuda; Yunus, Faizal Amin Nur; Razali, Mohd Nizamuddin; Rahim, Mohd Bekri; Abdul Rahman, Khairul Anuar (Research and Innovation in Technical and Vocational Education and Training, 2022)
This study is about the development of an Educational Video of Air Conditioning Workshop Practice using the YouTube platform. The production process of this development of Educational Video of Air Conditioning Workshop Practice using the YouTube platform is important to meet the needs of educational facilitators in the process of learning and teaching in the classroom. The purpose of the study was to design and develop an educational video of Air Conditioning Workshop Practice using a YouTube platform that is more interesting and effective for air-conditioning and refrigeration students. The ADDIE model which consists of five phases namely analysis, design, development, implementation, and testing is used as a guide in the development of this product. The sample of analysis from the questionnaire is tested on BBG cohorts 1-8 to analyse the functionality of the educational video of Air Conditioning   Workshop Practice using the YouTube platform. The results of the analysis show that all the respondent is very agreed with the design, content, language, and function of the Educational Video of Air Conditioning   Workshop Practice using the YouTube platform. It is hoped that this Educational Video of Air Conditioning Workshop Practice using the YouTube platform can help to facilitate education in the process of learning and teaching in the classroom. The development of digital media for learning such as video could improve the current practice of skills training in the field of TVET.